2023
DOI: 10.1001/jamahealthforum.2023.1090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Out-of-Pocket Spending on Ultra-Expensive Drugs in Medicare Part D vs Commercial Insurance

Abstract: ImportanceLittle is known about how out-of-pocket burden differs between Medicare and commercial insurance for ultra-expensive drugs.ObjectiveTo investigate out-of-pocket spending for ultra-expensive drugs in the Medicare Part D program vs commercial insurance.Design, Setting, and ParticipantsThis was a retrospective, population-based cohort study of individuals using ultra-expensive drugs included in a 20% nationally random sample of prescription drug claims from Medicare Part D and individuals aged 45 to 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Another limitation is that this study assessed beneficiaries enrolled in Traditional Medicare, which limits generalizability to men participating in Medicare Advantage or commercial insurance plans. Nonetheless, men with Traditional Medicare typically experience similar or higher cost‐sharing compared to men enrolled in Medicare Advantage and commercial plans 34 . This makes men enrolled in Traditional Medicare the most likely to be affected by high drug costs and where we would expect the effect of 340B to be most apparent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is that this study assessed beneficiaries enrolled in Traditional Medicare, which limits generalizability to men participating in Medicare Advantage or commercial insurance plans. Nonetheless, men with Traditional Medicare typically experience similar or higher cost‐sharing compared to men enrolled in Medicare Advantage and commercial plans 34 . This makes men enrolled in Traditional Medicare the most likely to be affected by high drug costs and where we would expect the effect of 340B to be most apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Medicare typically experience similar or higher cost-sharing compared to men enrolled in Medicare Advantage and commercial plans. 34 This makes men enrolled in Traditional Medicare the most likely to be affected by high drug costs and where we would expect the effect of 340B to be most apparent. Next, there may have been differences in how 340B hospitals operate that would not be captured using claims data and may be better assessed using qualitative methods, which others have done in a different context.…”
mentioning
confidence: 99%
“…DiStefano et al revealed that recent legislation establishing a $2000 out-of-pocket cap in Part D had the potential to lower out-of-pocket costs for more than 125,000 Part D beneficiaries who use ultra-expensive drugs and are ineligible for low-income subsidies, thus ameliorating increases in out-of-pocket spending when transitioning from commercial insurance to Part D. 8 …”
Section: Introductionmentioning
confidence: 99%
“…While there are numerous articles 5 , 6 , 7 , 8 , 9 discussing problems in Medicare, none have specifically identified issues by provider type and HCPC code to reduce expenditures. This paper aims to use generative AI to identify payment errors by provider type and HCPC code.…”
Section: Introductionmentioning
confidence: 99%